Sustainability Analysis of Environmental Waste Alleviation through Bioconversion using Black Soldier Fly Larvae: A Case Study in Depok City, Indonesia - Zulkifli, Sunarto; Jayanegara, Anuraga; Noorachmat, Bambang Pramudya; Fahmi, Melta Rini; Tandio, Tjondroargo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Depok City, Indonesia, faces significant challenges with a population of over 2 million people, substantially impacting waste issues, particularly food waste, contributing to global anthropogenic greenhouse gas emissions. To support sustainable development goals, it is crucial to reduce food loss. To address this problem, black soldier fly (Hermetia illucens) has emerged as a potential solution because of its ability to break down food waste into biomass. Nevertheless, environmental waste management faces challenges such as public awareness, infrastructure limitations, stakeholder engagement, and threats to long-term sustainability. This study aims to identify key leverage points for the sustainability of BSF (Black Soldier Fly) larvae utilization in waste management. The objective of this study was to identify the key sustainability factors. This study used RAPFISH (Rapid Appraisal for Fisheries) software to find the keys to sustainability. Results reveal that the sustainability status of the utilization of BSF for environmental waste managementis deemed to be “Relatively Sustainable”. The Department of Environmental and Cleanliness plays a pivotal role as a sustainability leverage for this program.